2005
DOI: 10.1007/s00127-005-0972-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Working Alliance Inventory (WAI) in a French primary care setting

Abstract: The WAI is shown to be applicable to primary care social work settings to measure the working alliance phenomenon and predict disruption of practitioner-client relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
9
1
1
Order By: Relevance
“…The discrepancies might be attributed to the version studied (full vs. short version) or the type of analyses conducted (CFA vs. EFA). For instance, Guedeney, Fermanian, Curt, and Bifulco (2005) confirmed the predictive value of the instrument on the quality of the working alliance evolution. Nevertheless, according to an exploratory factor analysis (EFA), they proposed a new factor structure in two orthogonal factors.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The discrepancies might be attributed to the version studied (full vs. short version) or the type of analyses conducted (CFA vs. EFA). For instance, Guedeney, Fermanian, Curt, and Bifulco (2005) confirmed the predictive value of the instrument on the quality of the working alliance evolution. Nevertheless, according to an exploratory factor analysis (EFA), they proposed a new factor structure in two orthogonal factors.…”
supporting
confidence: 70%
“…The analysis done on the 36 items of the WAI-C allowed extraction of three factors using Cattell's criterion, explaining 41.04% of the total variance. The first four eigenvalues were (Guedeney et al, 2005). Indeed, Kaiser's criterion suggested to extract 10 factors, explaining 61.80% of the total variance, and a parallel analysis suggested to consider 5 factors, explaining 45.20% of the total variance.…”
Section: Efasmentioning
confidence: 99%
“…The Working Alliance Inventory (WAI; Horvath & Greenberg, 1986) and its short versions (Hatcher & Gillaspy, 2006;Tracey & Kokotovic, 1989) operationalize Bordin's concept of the therapeutic alliance. While numerous studies demonstrated its significance for outcome evaluation (e.g., Keller, Zoellner, & Feeny, 2010;Webb et al, 2011), the factor structure is an issue of tremendous concern (Guédeney, Fermanian, Curt, & Bifulco, 2005). No study could confirm the original three-subscale structure referring to tasks, goals and bonds.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, De Vries et al utilised the Working Alliance Inventory‐Revised (WAI‐R) that was developed using Bordin’s conceptualisation of alliance comprised of mutual bonds (including trust), goals and tasks (Hatcher & Gillaspy, ; Holwerda et al, ; Horvath, ). The WAI‐R scale was initially developed for use in psychotherapy but has also been adapted for use in the medical field (Guédeney, Fermanian, Curt, & Bifulco, ). Trevino et al, Epstein et al, and Fenton et al used The Human Connection Scale (THC) (Epstein & Street Jr., ; Fenton et al, ; Mack, Wolfe, Grier, Cleary, & Weeks, ; Trevino et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Trust was frequently a subscale or measured by individual items within studies that measured the patient and oncologist that was developed using Bordin's conceptualisation of alliance comprised of mutual bonds (including trust), goals and tasks (Hatcher & Gillaspy, 2006;Holwerda et al, 2013;Horvath, 1994). The WAI-R scale was initially developed for use in psychotherapy but has also been adapted for use in the medical field (Guédeney, Fermanian, Curt, & Bifulco, 2005 2007; Fenton et al, 2018;Mack, Wolfe, Grier, Cleary, & Weeks, 2006;Trevino et al, 2014). This scale was developed specifically to measure the working alliance, defined as mutual understanding, caring and trust between patients and their oncologists.…”
Section: Relationship Dimensions and Measuresmentioning
confidence: 99%